Are Capital Controls Effective in the 21st Century? : The Recent Experience of Colombia - Clements, Benedict (IMF Working Papers; Working Paper, 2009)
This paper assesses the effects of capital controls imposed in Colombia in 2007 on capital flows and exchange rate dynamics. The results suggest that the controls were successful in reducing external borrowing, but had no statistically significant impact on the volume of non- FDI flows as a whole. We find no evidence that restrictions to capital mobility moderated the appreciation of Colombia's currency, or increased the degree of independence of monetary policy. We also find that controls have significantly increased the volatility of the exchange rate. Additional research is needed to assess the effects of capital controls on financial stability.